Fostering Gender Equality in China: Empowerment Strategies Used by the Voice of Women (English Translation) - Liang, Guanghan (Archīum Ateneo, 2019)
Media has radically transformed in the twenty-first century culminating in platforms for anybody and everybody to publicize news. A “news blog” called WeMedia offers people from different walks of life a space to publish an array of news. An increasing number of non-governmental organizations (NGOs) are using WeMedia to transmit agendas as a result of the popularity of new media technology. With new media communication being interactive, immediate, and polymerized, WeMedia communication can overcome the shortage of traditional media and maximize the communicating effect of the NGO. Through the Anti-Domestic Violence communication of China’s Gender Watch Women’s Voice (hereinafter referred to as the “Voice of Women”), this paper tackles WeMedia’s strategies and methods of empowerment via the concepts of media and gender. By classifying WeMedia into two types, social WeMedia and group WeMedia, this study found that the Voice of Women creatively used the news to fight for women’s rights. Using the theoretical system of empowerment (via the media and gender), this study attempts to summarize the strategies and methods of WeMedia empowerment through literature research and semi structured interviews.